Fall guys : false confessions and the politics of murder - Fisher, Jim, 1939- (Southern Illinois University Press, 1996)
There was horror enough in the brutal slayings of two western Pennsylvania women, but when a malevolent detective framed two innocent boys in these unrelated cases, the evil compounded. In a compelling story of criminal detection written by the investigator himself, former FBI agent Jim Fisher provides the anatomy of an outrage. In the first of the cases, eleven-year-old Charlie Zubryd confessed that at the age of eight, he had murdered his widowed mother by shattering her skull with a hatchet. The crime was committed in the basement of the modest Zubryd home in a rural section of Sewickley Township in western Pennsylvania, not far from Pittsburgh. Following intense police questioning, young Zubryd confessed to the crime in March 1959, a full twenty-eight months after the bloody murder of his mother.